Soy protein isolate prevents chemically-induced rat mammary tumors - Constantinou, AI; Lucas, LM; Lantvit, D; Hawthorne, M; Xu, XY; Nho, CW; Jeffery, EH; Christov, K; van Breemen, RB; Pezzuto, JM (TAYLOR & FRANCIS LTD, 2002)
Previous studies have shown an inhibitory effect of soy on mammary carcinogenesis, but it is unclear which component of soy provides this beneficial effect. The present study was undertaken to compare the anti-tumor effects of soy protein isolate and those of its isoflavones: genistein and daidzein. Six groups of female Sprague-Dawley rats were fed modified corn starch AIN76A diets supplemented with: no additional agents (control); purified genistein at 200 mg/kg diet; purified daidzein at 200 mg/kg diet; a combination of genistein and daidzein at 100 mg/kg diet each; soy protein isolate enriched in isoflavones (SPI+); or soy protein isolate depleted of isoflavones (SPI-). Mammary carcinomas were induced by 7,12-dimethylbenz[a] anthracene (DMBA) injected one week after the animals started eating the experimental diets. At the end of the study (120 days post-DMBA treatment), no significant differences were found among the six groups with respect to tumor incidence or survival. However, there was a significant (p < 0.05) reduction in tumor multiplicity in the daidzein (5.45) and SPI+ (5.45) groups, when compared to the control group (8.05). The most effective diet was the SPI-, which produced a highly significant (p < 0.01) reduction in tumor multiplicity (4.05). Tumor latency was increased from 53 days in the control group to 68 days in the daidzein group and to 72 days in the SPI- group. Both SPI groups, but not the genistein or daidzein groups, up-regulated transcriptional expression of the antioxidant enzymes NAD(P)H:quinone reductase (QR) and glutathione S-transferase (GST) Ya2. These results suggest that the mode of chemopreventive action of soy protein isolate is distinct from that of the main soy isoflavones. Furthermore, isoflavone-depleted soy may be more beneficial than isoflavone-enriched soy in preventing mammary tumors in these experimental animals.
Keywords: DNA STRAND BREAKAGE; BREAST-CANCER RISK; CELL-DIFFERENTIATION; QUINONE REDUCTASE; IN-VITRO; TOPOISOMERASE-II; GENISTEIN; CARCINOGENESIS; ISOFLAVONES; TAMOXIFEN